Robust Model Predictive Control with Signal Temporal Logic constraints for Barcelona Wastewater System. Issue 1 (July 2017) - Farahani, Samira S.; Zadeh Soudjani, Sadegh Esmaeil; Majumdar, Rupak; Ocampo-Martinez, Carlos
Abstract: We propose a traceable approach for the control of the Barcelona wastewater system that is subject to sudden weather-change events within the Mediterranean climate. Due to the unpredictable weather changes, lack of appropriate control methodologies may result in overflow in the sewage system, which causes environmental contamination (pollution). In order to improve the management of the wastewater system and to reduce the contamination, we propose robust model predictive control, which is an online control approach that designs the control actions (i.e., flows through network actuators) under the worst-case scenario while minimizing the associated operational costs. We employ signal temporal logic to specify the desired behavior of the controlled system once an overflow occurs and encode this behavior as constraints so that the synthesized controller reacts in time to decrease and eliminate the overflow. We apply our proposed technique to a representative catchment of the Barcelona wastewater system to illustrate its effectiveness.